PERANCANGAN APLIKASI PILKADA TANGERANG SELATAN BERBASIS ANDROID DENGAN METODE USER CENTERED DESIGN - Iqbal Samsudin; Dani Dani (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT An electronic election is a method used in the poll effort for decision-making. The electronic election activity is intended to aggregate voting rights aimed at finding the best solutions to the problem of choice. The electronic election activities on the people known to be public elections or elections held by the election, but this electronic selection can also be used on smaller domes like the rt's fogi.the research on these rt feeds. researchers take the user centered design method to develop more efficient systems for further development in the selection the south's tangent. The system is designed with a web view android base for voter panels and web site bases for admin panels with HTML programming languages and PHP and mysql as data storage. Based on implemented system tests and the results of the system usage questionnaires, researchers conclude that the system of the selected application system is already qualified for use. Southern communities are easier to access information about potential local heads, as well as electoral processes in determining their heads. Keywords : Electronic Selection Applications, UCD, E-mobile Voting.